Comparative Advantage and the Equilibrium Rate of Unemployment - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 1991)
This paper develops a two-country Heckscher-Ohlin model with endogenous equilibrium involuntary unemployment to examine the question: What is the effect of free trade on the equilibrium rates of unemployment in the labor abundant and labor-scarce countries? It is shown that free trade leads to a decline in the equilibrium rate of unemployment in the labor-abundant country but to a rise in unemployment in the labor-scarce country.